Impact of CYP2C19 Variants on Clinical Efficacy of Clopidogrel and 1-Year Clinical Outcomes in Coronary Heart Patients Undergoing Percutaneous Coronary Intervention - Sun, Hong; Qu, Qiang; Chen, Zhen-Fan; Tan, Sheng-Lan; Zhou, Hai-Jun; Qu, Jian; Chen, Hui (Frontiers in Pharmacology, 2016)
The impact of pharmacogenetic variants of cytochrome P450 2C19 (CYP2C19) on clopidogrel-mediated effects on platelet inhibition, inflammatory response and endothelial function, as well as risk of major adverse cardiovascular events (MACE), in coronary heart patients undergoing percutaneous coronary intervention (PCI) was investigated. To this end, we assessed the residual platelet aggregation rate (RPA), maximal aggregation rate (MAR) and plasma levels of sCD40L, sP-selectin, MMP-9, sVCAM-1 and sE-selectin after 24 h of PCI in 559 patients treated with clopidogrel and followed up for one year for evidence of MACE. CYP2C19 *2 and *3 variants were identified using a clopidogrel-sensitive gene detection kit. Our results showed higher RPA and MAR as well as increased sE-selectin, sCD40L, sP-selectin, MMP-9 and sVCAM-1 levels in CYP2C19 intermediate metabolizer (IM, CYP2C19*1/*2 or *1/*3), poor metabolizer (PM, CYP2C19*2/*2, *2/*3 or *3/*3) and combined IM+PM groups, relative to those in extensive metabolizers (EM, CYP2C19*1/*1). In total, 519 patients completed one year of follow-up, among which 69 (13.3%) experienced MACE. The risk of MACE in CYP2C19 IM+PM patients was 2.664 times higher than that in CYP2C19 EM patients (OR=2.664(1.397–5.193), P=0.004). The data suggest that CYP2C19*2 and *3 variants modulate the drug efficacy of clopidogrel in coronary heart patients undergoing PCI and further enhance the risk of MACE. Accordingly, CYP2C19 pharmacogenetic profiling may be beneficial for coronary heart patients undergoing PCI to predict the efficacy of treatment with clopidogrel. We propose that IM and PM patients should benefit from treatment with higher clopidogrel doses to improve efficacy and reduce the incidence of MACE.